Phosphate fertilizers and bioactivator in cotton crop (Research, Society and Development, 2023)
The experiment evaluated the application of phosphatic fertilizers and bioactivator, verifying their effects on the components of cotton production. Two experiments were carried out, both with a randomized complete block design, in a factorial scheme (2x5 in experiment I and 3x5 in experiment II). The experiment I used 02 phosphatic sources with 05 doses of triple superphosphate 0, 72, 143, 214 and 286 kg ha-1 and bioactivator 0, 300, 600, 900 and 1200 g ha-1. Experiment II used 5 doses of magnesium thermophosphate (0, 133, 267, 533 and 1067 kg ha-1), triple superphosphate (0, 57, 114, 228 and 455 kg ha-1) and bioactivator (0, 240, 480, 960 and 1920 g ha-1). All analyzes were performed with the aid of SAS®. The data were submitted to analysis of variance and compared by means of the Tukey test, 5% probability for comparison between sources and regression analysis for the doses. Phosphate fertilizer and bioactivator applications, in both conditions studied, did not influence the characteristics evaluated (mean mass of the bush, mass of 100 seeds and yield of fibers). In soils with low phosphorus content, the bioactivator and triple superphosphate presented similar behavior on the yield of cotton. The bioactivator, in soils with high phosphorus content, provided the maximum productivity with the dose 900 g ha-1 and the highest economic return with the dose of 870.87 g ha-1. The thermophosphate, in soils with low phosphorus content, provided the maximum productivity in the dose of 96 kg ha-1 of P2O5 and the highest economic return in the dose of 84.40 kg ha-1 of P2O5.